THE EFFECT OF GCG MECHANISM AND CSR ON FINANCIAL PERFORMANCE - Retno Santi Nur Azizah; Syamsul Huda (FKIP Unswagati, 2023)
This study aims to determine and examine The Effect of independent commissioners, managerial ownership, audit committees, and corporate social responsibility on financial performance both partially and simultaneously (together) in Textile and Garment Sub Sector Companies listed on the Indonesia Stock Exchange Period 2017-2021. The data analysis technique in this research is descriptive and verification. Testing the hypothesis using a multiple linear regression analysis model. The study results show that some GCG components affect financial performance, and others do not. The independent board of commissioners and audit committee do not affect ROA. Managerial ownership and CSR affect ROA. Then the independent board of commissioners also does not affect EPS. Managerial ownership, audit committee, and CSR affect EPS. Together the independent board of commissioners, managerial ownership, audit committee, and, CSR affect ROA and EPS in textile and garment sub-sector companies for the 2017-2021 period.